A Pedagogy of Inquiry for the Promotion of ‘Caring Thinking’ for Muslim Philanthropy - Hussien, Suhailah (2020)
Pro social behaviours such as perspective taking, sharing, caring, and helping are emphasised in early childhood education with the aim of developing altruistic values. Inquiry based pedagogy has been found to be most effective in inculcating these pro social behaviours (Villardon-Gallego, Garcia-Carrion, Yanez-Marquina & Estevez, 2018). Studies on programmes that use an inquiry based learning, such as Philosophy for Children (P4C) programmes have shown that children as young as three-year-old have been engaged in the method with positive results (Haynes & Murris, 2019). Hence, I would like to share a case of how Hikmah pedagogy, a pedagogy that has been adapted from P4C, was used to promote caring thinking among pre-schoolers. The case looks at how moral inquiry and reasoning was used to engage children to think and care about others, planting the seeds of philanthropy.